INVESTIGATION ON BIO-ELECTROMAGNETIC FIELD OF TERAHERTZ RADIATION BEHAVIORS AT THE INTERFACE OF BRAIN-FAT TISSUE - Muhamad Hamdi (UII, 2012)
Analysis at a boundary of brain-fat tissue has been concerned with use of terahertz radiation for fundamental studies in cellular organization and as tools in medical practice. The penetration in these two tissue is analyzed by means of numerical analysis. The 0.1-10 THz gap radiation frequency range is used for realistic theoretical analysis while it is compared to the 0.1-10 MHz and 0.1-10 GHz radiation frequency , respectively. The result of dielectric constant for brain and fat show remain constant for all frequencies in ultrasound and microwave ranges which describe dependence of dielectric constant on frequency. The sharp decrease of K in this specific THz range due to its phenomena absorbs water strongly in near infrared rotational-vibrational spectra and brain tissue included a kind of dielectric medium loss. In addition to in fact the brain tissues consist of most of glucose contained discrete tissue structures relate to water content. The result of the numerical calculation in the THz-MHz signal radiation penetration in interface of brain-fat tissue indicates reduction of electric field intensity amplitude ratio values is caused by properties of dielectric loss tissue from fat ( K = 100 ) to brain (K = 200) and also this radiation absorbs water strongly in the liquid contained tissues. The ratio of magnetic and electric field intensity amplitude is a rise linearly with increasing ranges of higher frequencies. This fact caused besides the higher frequency the higher magnetic field intensity, also THz radiation transmission includes light emissions traveling in a straight line. Keywords: brain-fat tissue, dielectric loss medium, interface, penetration, THz radiation